Les réseaux personnels dans les parcours professionnels des animateurs jeunesse - Julien Virgos (Nantes Université, 2020)
Resulting from a thesis work in progress, this article addresses the question of the influence of personal networks on the career paths of youth workers in terms of hiring. We present our articulation of the work devoted to professional socialization and the study of the pathways, before specifying how the taking into account of the time and the personal networks seems to us paramount in the frame of our works. The analysis of the hiring sequences in the individual courses of thirty-one animators highlights the role that personal networks can play in them. The framework of the Sciences of Education and Training, in which our work is part, allows a multireferential approach (Ardoino, 1993) and an apprehension of the complexity of the professionalization process among youth workers.